PENGUATAN KELEMBAGAAN PETANI BARAMBAN DALAM PEMASARAN SAYUR SEHAT BERSERTIFIKAT PRIMA 3 DI KECAMATAN BANUHAMPU KABUPATEN AGAM, SUMATERA BARAT - Melinda Noer; Herviyanti Herviyanti; Trimurti Habazar; Cesar Welya Refdi (Jurnal Hilirisasi IPTEKS, 2021)
The Baramban Farmers Group, since 2014, has been carrying out healthy vegetable farming with vegetable products that have been certified Prima 3. However, until now, the management of healthy vegetable farming by the Baramban Farmers Group in Banuhampu District, Agam Regency has not experienced much development in farming because it has not created a broad market with prices that favor the welfare of farmers. Strengthening farmer institutions in marketing healthy vegetables is thus very important and have become an essential element in developing healthy vegetable agribusiness in local, national, and even global markets. The method used is counseling, coaching and mentoring. This service activity is planned to be carried out over the next five years, starting with building a cooperation agreement with the Baramban farmer group starting in 2020. Several alternative solutions to solve the problems of healthy vegetable farmer group partners proposed and agreed upon by the Baramban Farmer Group are: a. Carry out mentoring activities for healthy vegetable farmers by transferring resources from universities through integrated science an agribusiness perspective, b, empowering farmers based on group institutional strengthening to build collective action that is independent of farmers to drive healthy vegetable markets, c. Facilitate farmers to create healthy vegetable market segments through modern markets and online markets with information technology 4.0 and 4. Building partnerships with Transmart as a modern market on a national scale and has a global-scale marketing network. The conclusion is that farmer groups are willing to become partners of the Community Service Team in a community partnership program scheme to help businesses develop.